THE LEVERAGE OF THE POWER OF TWO METHOD IN ENHANCING STUDENTS LEARNING OUTCOME IN AKEEDAH AKHLAK (MORAL THEOLOGY)AT MTS MANBATUL FIKRI CURUGRENDENG - Afif Nurseha; Dewi Gita Permani (International Journal of Teaching and Learning, 2023)
This study is motivated by the low student learning outcomes specifically in Akeedah Akhlak or moral theology subject. It was due to the limitation of learning method use in and monotonous method that the students have a little to no interest in participating the teaching and learning process. Therefore, this study aims to explore the reality, the leverage or influence along with the relation between the use of the power of two method with students learning outcome in MTs Manbatul Fikri Curugrendeng. Quantitative method is used in this research particularly by implementing the pre-experimental design in which involves one group pretest and posttest. The subject of the research are students in class VIII Mts Manbatul Fikri Curugrendeng. Based on the results, the reality data obtained of 3.59. The value indicates the efficacy of a certain method. In this case, there is reality of the power of two implementation in the research site. The result from t-test obtained sig. 0.000 < 0.05 meaning that there is leverage of the power of two method to students learning outcome. Furthermore, the correlation test shows that there is correlation between the two variables evidently by the value reach 0.008 <0.05. therefore, it is safe to conclude that there is correlation between the power of two method with students learning outcomes.